STRATEGI KOMUNIKASI PEMASARAN DIGITAL CUT PONSEL MELALUI TIKTOK DALAM PENINGKATAN PENJUALAN SMARTPHONE - Raudhatul Jannah; Ainol Mardhiah; Ade Muana Husniati; Anismar Anismar; Muhammad Fazil (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2026)
Cut Ponsel Store is a business engaged in the sale of smartphones and mobile phone accessories located in Krueng Mane, Muara Batu District, North Aceh Regency. The background of this study is based on technological developments and the increasing use of social media as a means of marketing communication, which has encouraged businesses to adapt in the face of business competition. This study aims to determine the marketing communication strategies used by Cut Ponsel Store through TikTok social media to increase smartphone sales. This study uses a qualitative descriptive approach. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation. Informants in this study consisted of the owner of Cut Ponsel Store, store promoters, and several consumers who had made purchases. Data analysis was conducted based on the marketing mix concept, which includes product, price, place, and promotion. The results of the study show that Cut Ponselstore implements a direct marketing communication strategy and utilizes the social media platform TikTok as its main promotional tool. In terms of products, Cut Ponsel store offers a variety of smartphone brands with guaranteed quality. In terms of price, information is conveyed transparently and competitively. The store's strategic location makes it easy for consumers to visit in person. Meanwhile, sales promotions in the form of discounts, cashback, and additional bonuses are the main factors in increasing consumer interest in purchasing. The obstacle faced is the limited variety of promotional content. The conclusion of this study shows that the implementation of a marketing mix supported by sales promotions can increase smartphone sales at Cut Ponsel store.